Study the Histopathogic Effects of Arsenic Trioxide on Some Parenchymatous Organs of Male Rats and Under Alphalipoic Acid - Khalil H. Aljeboori 1 , Khalil Gzar2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was designed to evaluate the histopathogical effects of arsenic trioxide (ATO) on the some organsof rats , for this reason group of rats (15) were I/P inoculated with 1.5 mg /Kg .B.wt . daily for 30 days othergroup( 15 rat) treated with 100 mg/kg.B.wt of alphalipoic acid and ATO ( 1.5 mg/ kg.B.wt) for 30 .Theresults was revealed that the extensive pathological lesions in the liver , kidney , spleen and testes in all ratsexposed to arscenci trioxide due to the pathotoxic effect of ATO and decreased lesions were in the grouptreated with the alpha lipoic acid .100 mg / kg .B.wt) for 30 days as ameliorative or protective effect againstpathotoxicity of ATO .